Character Downfall through Alcoholism: A Study of Crane’s Maggie a Little Girl of The Streets - Ali, Muhammad Ilham (Universitas Veteran Bangun Nusantara, 2025)
This study examines the impact of alcoholism on the characters in Stephen Crane’s Maggie: A Little Girl of the Streets, set in the slums of 19th-century New York City. The novel portrays the struggles of its characters against poverty, violence, and alcoholism, highlighting the harsh realities of urban life. Utilizing a qualitative descriptive method and an objective approach, this analysis focuses on the intrinsic elements of the novel, exploring how alcoholism influences the behaviour, relationships, and fates of characters such as Maggie, Jimmie, Mrs. Johnson, and Pete. Through detailed character analysis and examination of direct quotes from the text, the study reveals the profound effects of alcoholism on the characters' lives. Maggie, once depicted as innocent and hopeful, falls victim to exploitation and despair due to her family's alcoholism and societal pressures. Jimmie, shaped by a violent environment, transforms into a harsh and callous individual. Mrs. Johnson’s alcohol dependency leads to instability and violence within the family, while Pete, initially perceived as a potential saviour for Maggie, reveals himself as exploitative and opportunistic, contributing to her downfall. The study concludes that alcoholism acts as a catalyst for the characters' tragic fates, emphasizing the devastating consequences of their struggles against the backdrop of societal challenges. This analysis contributes to a deeper understanding of how societal and familial influences, particularly alcoholism, shape character development and lead to inevitable tragedy in Crane’s novel.